Effect of Long-Range Transported Fire Aerosols on Cloud Condensation Nuclei Concentrations and Cloud Properties at High Latitudes - Kommula, Snehitha Manaswini; Buchholz, Angela; Gramlich, Yvette; Mielonen, Tero; Hao, L.; Pullinen, Iida; Vettikkat, Lejish; Ylisirniö, Arttu; Joutsensaari, J.; Schobesberger, Siegfried; Tiitta, P.; Leskinen, Ari; et al. (American Geophysical Union, 2024)
Active vegetation fires in south-eastern (SE) Europe resulted in a notable increase in the number concentration of aerosols and cloud condensation nuclei (CCN) particles at two high latitude locations—the SMEAR IV station in Kuopio, Finland, and the Zeppelin Observatory in Svalbard, high Arctic. During the fire episode aerosol hygroscopicity κ slightly increased at SMEAR IV and at the Zeppelin Observatory κ decreased. Despite increased κ in high CCN conditions at SMEAR IV, the aerosol activation diameter increased due to the decreased supersaturation with an increase in aerosol loading. In addition, at SMEAR IV during the fire episode, in situ measured cloud droplet number concentration (CDNC) increased by a factor of ∼7 as compared to non-fire periods which was in good agreement with the satellite observations (MODIS, Terra). Results from this study show the importance of SE European fires for cloud properties and radiative forcing in high latitudes. ISSN:0094-8276 ISSN:1944-8007